The Robot Factory Pseudoscience in Education and Its Threat to American Democracy - Ganem, Joseph (Springer International Publishing, 2018)
Fake Science Is Killing Our Schools-and Our Republic Science is both a method for understanding and a guide for decision-making. It can and should be the foundation for citizenship: logic, reasoning, challenging claims, making choices based on verifiable fact. Authentic science education is key to producing informed, engaged citizens. It can't be separated from the culture in which it operates. Instead, we're in the most vicious cycle imaginable for a democracy-but perfect for a corporatist kleptocracy. With agenda-driven leaders using pseudoscience to justify bad educational policy, education has become a dehumanizing tool for mass producing compliant workers who accept what they're told and do what they're asked. Physicist and educator Dr. Joseph Ganem rips the lid off of this neatly-packaged scam. He exposes the dangers of pseudoscience in the hands of decision-makers, educators, and students. In nothing less than a compelling new vision for 21st century education, he calls us to reject pseudoscience in all forms, engage in a collective search for truth, and commit to an authentic education for every child. "Dr. Ganem nails it! He brings a scientist's eye and a crusader's passion to explaining how "reformers" are killing an education system that once was-and still could be-the envy of the world." --John Owens, author, Confessions of a Bad Teacher: The Shocking Truth from the Front Lines of American Public Education "Empowering and enlightening. Sparks will fly when people read this book - so policymakers be forewarned (or better be ready)! There will be a revolution - a powerful call for change." --CJ Westerberg, Founder & Editor, The Daily Riff: Be Smarter. About Education.